ANALISIS PENGUASAAN KATA KERJA “TING SHUO” DAN “JU SHUO” PADA MAHASISWA 2016 BAHASA MANDARIN UNTAN - Meidia Dwi Cahyani; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractVerbs are the most commonly used syntax in Chinese expressions. Verbs denote each action or action. Take the verbs "jushuo" and "tingshuo" as examples. These two words are often heard and seen by us. There are some differences in the usage of these two words, which makes students incorrect  on using them. In order to understand the mastery and difficulties of verbs "jushuo" and "tingshuo" by Tanjungpura University FKIP Untan Chinese Education Program batch 2016 students, the author uses the test method to test the students in order to understand their mastery of these words and analyze the difficulties in learning "jushuo" and "tingshuo". The test results show that the subjects have mastered some of the usages of these two modalities well, but some of them have not been mastered yet. The correct rate of "jushuo" is 55.32%. For example, "Is it true that Mike is supposed to hold a personal painting exhibition next month?" The correct rate of "tingshuo" is 63.76% of them, for example, "Children have heard stories about Monkey King's disturbance of the Heavenly Officials" have mastered them well. Key words: Allegation, Mastery Analysis,  Said and Heard，Verb